Estudo de bioensaios e métodos cromatográficos para avaliação de potência/teor de toxina botulínica tipo A - Xavier, Bruna (2022)
Botulinum neurotoxin type A (BoNTA) belongs to a family of toxins which are produced by Clostridium botulinum. Their clinical use was approved in 1989 and since then, was used for therapeutic and aesthetic purposes. In the present study, a cell culture in vitro bioassay based on the cell line of adenocarcinoma T-47D, was studied and validated for the potency assessment of BoNTA in biopharmaceutical formulations. The validation studies showed that the bioassay is specific, accurate, repeatable and robust, and can be applied for the content/potency assessment of BoNTA. The results were compared with those of the LD50 bioassay pharmacopeial method, showing mean values 1.08% higher. The variance analysis (ANOVA) showed non-significant differences between the methods, at the level of significance of 5% (p = 0.05). The analysis of BoNTA in pharmaceutical products from different manufactures were analyzed by size exclusion and reversed-phase liquid chromatography, giving mean values 1.15% higher and 0.85% lower, respectively, compared to the T–47 cell culture bioassay. Besides, stability studies were carried out for evaluate the integrity of the biomolecule during the storage period of 36 months. The analysis showed decrease of the content of BoNTA, and allowed to quantify the higher molecular weight proteins and related proteins generated, that were lower than 3.63 and 1.10%, respectively. In this context, the study performed by physicochemical and biological methods represents an advance for the characterization, and evaluation of identity, purity, potency and stability of these biotechnology products. The methodologies can be applied for the production steps, purification and quality control, to ensure batch-to-batch consistency of BoNTA. Besides, represent important contribution in the context of the development of alternative methods to use of animals for the potency assessment of BoNTA, improving the quality control of biopharmaceutical formulations.